Cardiac tamponade due to primary malignant pericardial mesothelioma diagnosed with surgical pericardial resection. Issue 4 (October 2021) - Kawakami, Naoki; Kawai, Miki; Namkoong, Ho; Arai, Daisuke; Ueda, Soichiro; Hamada, Kenichi; Kawada, Ichiro; Hasegawa, Naoki; Mikami, Shuji; Asamura, Hisao; Fukunaga, Koichi
Abstract: Primary malignant pericardial mesothelioma is an extremely rare disease. Malignant disease of the pericardium is an infrequent cause of cardiac tamponade. Hence, cardiac tamponade in the context of primary malignant mesothelioma of the pericardium is an uncommon clinical scenario. A 67-year-old male patient, an ex-smoker, complaining of progressive lethargy was referred to a hospital for investigation of persistent pericardial effusion. The pericardial fluid cytology was categorized as class Ⅲ. Thereafter, he was referred to our hospital for further evaluation. Fluorodeoxyglucose (FDG) positron emission tomography (PET) revealed FDG accumulation in the pericardium and mediastinal lymph node. Surgical biopsy of the pericardium was performed through a subxiphoid approach for a definitive diagnosis. Histopathological examination revealed diffuse infiltration of the pericardium by a malignant tumor consisting of epithelioid cells with large round nuclei and prominent nucleoli, arranged in a tubular papillary pattern. Finally, the patient was diagnosed with primary malignant pericardial mesothelioma of epithelioid type. The patient died 6 weeks after admission. This diagnosis must be considered in patients having unexplained massive pericardial effusion. Furthermore, we should consider prompt cytological analysis and FDG PET to arrive rapidly at a definitive diagnosis to administer combination chemotherapy that may provide clinical benefit. <Learning objective: Primary malignant pericardial mesothelioma is a rare disease. Malignant disease of the pericardium is an infrequent cause of cardiac tamponade. Hence, cardiac tamponade in the context of primary malignant mesothelioma of the pericardium is an uncommon clinical scenario. However, this diagnosis must be considered in patients having unexplained massive pericardial effusion. Furthermore, we should consider prompt cytological analysis and fluorodeoxyglucose positron emission tomography to arrive rapidly at a definitive diagnosis to administer combination chemotherapy that may provide clinical benefit.>